Stable Extent of Recurrently Active Cardiac and Cutaneous Sarcoidosis - Patterson, Karen C.; Rosenbach, Misha; Bravo, Paco E.; Dubroff, Jacob G. (Frontiers in Medicine, 2021)
Background: Recurrent or persistently active sarcoidosis is a risk factor for permanent organ damage. Whether this damage is due to accumulated focal injuries or progressive disease extent is not known, as the natural history of chronic inflammation in sarcoidosis is poorly characterized. The objective of this study is to determine the pattern of disease in recurrently active sarcoidosis. Methods: We identified patients with recurrent cardiac sarcoidosis (N=21) retrospectively from an imaging database, and with recurrent cutaneous sarcoidosis (N=17) from a prospective registry. The longitudinal patterns of cardiac sarcoidosis were established by findings on cardiac positron emission tomography scans, and of cutaneous sarcoidosis by the validated Cutaneous Sarcoidosis Activity and Morphology Instrument clinical scoring system. Patterns of recurrent disease were compared to baseline findings. Results: Recurrent sarcoidosis occurred in a nearly identical pattern and distribution as baseline disease, and spread of disease was rarely observed for both cardiac and cutaneous sarcoidosis: 97% of heart segments positive on recurrence scans were positive on baseline scans, and only one new region of facial disease was observed. In some cases, recurrence followed years of apparent remission. Discussion: Across phenotypes, and across a long period of follow-up, the extent of sarcoidosis was stable in spite of fluctuations in disease activity. For patients with a demonstrated history of recurrent disease affecting critical organs, our findings support the need for long-term follow-up.